Ibnu Taimiyah and Qurais Shihab's Views on the Law of Electing Non-Muslim Leaders: A Comparative Study - Katimin, Katimin; Adenan; Anzaikhan, M. (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2024)
Ideally, the selection of leaders in a multicultural country should be a political issue free from the subjectivity of religious beliefs. In reality, however, the urgency of faith and political interests are often mixed, leading to friction within society, including in Indonesia. This gap is intriguing to study, especially how Indonesian Muslims perceive the existence of non-Muslim leaders within the context of Islamic Law. To address this gap, this article examines the thoughts of two figures with substantially opposing views, namely Ibn Taymiyyah and Qurais Shihab. This article falls under library research with a qualitative approach. The methodology used is a comparative study. The results of the research conclude that Ibn Taymiyyah, a classical scholar, emphasizes the importance of a leader's faith and piety, as well as their ability to uphold Sharia law. According to him, a leader must be a Muslim capable of safeguarding and protecting the interests of the Muslim community. However, Qurais Shihab, a contemporary intellectual, offers a more contextual and inclusive perspective. He emphasizes universal values such as justice, welfare, and the common good. Qurais Shihab acknowledges that in the modern socio-political context and pluralism, a non-Muslim leader can be accepted if they are able to ensure justice and the welfare of society.